ХИНДИ ТІЛІНДЕГІ СИНОНИМДЕРДІҢ АНЫҚТАМАЛАРЫ МЕН ЖАСАЛУ ЖОЛДАРЫ - Кокеева, Д. М. (Journal of Oriental Studies, 2016)
В статье рассматриваются определение, способы образования и отличительные черты синонимов в языке хинди. The article deals with the definition, methods of education and the distinctive features of synonyms in Hindi language.